2013
DOI: 10.1242/jcs.136440
|View full text |Cite
|
Sign up to set email alerts
|

A novel human receptor involved in bitter tastant detection identified using the model organism Dictyostelium discoideum

Abstract: SummaryDetection of substances tasting bitter to humans occurs in diverse organisms including the social amoeba Dictyostelium discoideum. To establish a molecular mechanism for bitter tastant detection in Dictyostelium, we screened a mutant library for resistance to a commonly used bitter standard, phenylthiourea. This approach identified a G-protein-coupled receptor mutant, grlJ 2 , which showed a significantly increased tolerance to phenylthiourea in growth, survival and movement. This mutant was not resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, although TAS2 receptors are involved in bitter taste perception in mammals, perhaps other molecular targets may also be involved in Dictyostelium and mammalian systems. An example of this is provided by a recent study investigating novel targets of a standard strong bitter tastant, phenylthiourea (PTU), in Dictyostelium, where the bitter tastant inhibited cell movement (Robery et al, 2013), and a genetic screen identified a PTU-sensitive receptor with homology to a poorly characterized human GABAB protein, where the human protein restored the sensitivity to PTU in Dictyostelium (Robery et al, 2013). Another study, again in Dictyostelium, identified an ion channel (PDK2) to be targeted by a bitter taste-related compound, naringenin (Glendinning, 1994), a flavonoid found in high levels in citrus fruit (Waheed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations